Sense of life and mathematization of culture - Gómez-Chacón, Inés (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The articulating theme as indicated in the title is the sense of life. A series of reflections on the relationship of the person with the mathematization of culture is offered. The scientific knowledge of the world is not banal, but rather based on it the person in his «will to sense» looks at that reality with which he interacts. Delving into the meaning of some mathematical-technological phenomena related to artificial intelligence, capturing the social messages that occur and penetrating their deep sense can offer us keys to the understanding (and self-understanding) of the person in their being in the current society.
Keywords: mathematics; philosophy of mathematics; artificial intelligence; sense of life; humanoids; big data